Capital and Inequality in Rural Papua New Guinea - Beer, Bettina; Schwoerer, Tobias (Asia-Pacific Environment Monographs, 2022)
That large-scale capital drives inequality in states like Papua New Guinea is clear enough; how it does so is less clear. This edited collection presents studies of the local contexts of capital-intensive projects in the mining, oil and gas, and agro-industry sectors in rural and semi-rural parts of Papua New Guinea; it asks what is involved when large-scale capital and its agents begin to become significant nodes in hitherto more local social networks. Its contributors describe the processes initiated by the (planned) presence of extractive industries that tend to reinforce already existing inequalities, or to create and socially entrench novel inequalities. The studies largely focus on the beginnings of such transformations, when hopes for social improvement are highest and economic inequalities still incipient. They show how those hopes, and the encompassing socio-political transformations characteristic of this phase, act to produce far-reaching impacts on ways of life, setting precedents for and embedding the social distribution of gains and losses. The chapters address a range of settings: the PNG Liquid Natural Gas pipeline; newly established eucalyptus and oil palm plantations; a planned copper-gold mine; and one in which rumours of development diffuse through a rural social network as yet unaffected by any actual or planned capital investments. The analyses all demonstrate that questions around land, leadership and information are central to the current and future social profile of local inequality in all its facets.